2019
DOI: 10.1080/17461391.2019.1635649
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels of selected cytokines and microRNAs in response to vitamin D supplementation in ultra‐marathon runners

Abstract: Ultra-marathon (UM) running is an extreme endurance exercise. However, the mechanisms triggered with its practice remain unclear. While it is documented that strenuous physical activity activates immune responses and vitamin D plays a role in immune system suppression, data on the relationship between vitamin D status and cytokine profile in athletic populations are limited. To analyse the relative mRNA expression levels of selected pro-inflammatory cytokines (IL-1β, IL-6, IL-8, IL-17, TNF-α), COX-2, vitamin D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Indeed, there is a growing body of evidence implicating non-coding RNAs (ncRNAs) critical role in regulation, which supports the ongoing revolution lead by Mattick and colleagues [1,2]. Whilst our previous work and review focussed on microRNAs [3][4][5][6][7][8], other emerging regulatory ncRNAs, such as the long non-coding RNAs (lncRNAs), are increasingly studied and found to have a profound effect on cellular processes [9]. Their potential regulatory influence on exercise biology and exercise-related phenotypes warrants thorough investigation.…”
mentioning
confidence: 76%
“…Indeed, there is a growing body of evidence implicating non-coding RNAs (ncRNAs) critical role in regulation, which supports the ongoing revolution lead by Mattick and colleagues [1,2]. Whilst our previous work and review focussed on microRNAs [3][4][5][6][7][8], other emerging regulatory ncRNAs, such as the long non-coding RNAs (lncRNAs), are increasingly studied and found to have a profound effect on cellular processes [9]. Their potential regulatory influence on exercise biology and exercise-related phenotypes warrants thorough investigation.…”
mentioning
confidence: 76%
“…In a study evaluating cytokines and other inflammatory markers before and 12 h after running a 100 km run in amateur ultra-marathon runners, the researchers [ 16 ] applied a vitamin D supplementation protocol to part of the study participants. Thus, it was observed that the daily use of 10,000 IU of vitamin D for 2 weeks generated a significant reduction in circulating levels of IL-1β and an increase in circulating TNF-α and miR-155 after the 100 km course compared to pre-collection running, whereas in the group without supplementation no such trend was observed (Fig.…”
Section: Exercise Vitamin D and Immune Systemmentioning
confidence: 99%
“…Also, studies have shown increased levels of the immune system’s constituents that are related to the defense of respiratory viral infections [ 15 ]. Further, a study suggested that the association of regular physical exercises and vitamin D supplementation was related to a notable reduction of proinflammatory markers such as cytokines [ 16 ], an effect that could be useful in combating the cytokine storm from Covid-19.…”
Section: Introductionmentioning
confidence: 99%
“…Ludwig and co-workers showed seasonal differences in the expression of immune-connected miR-181, miR-21, miR-29 and let-7 family members [ 138 ]. In a study of ultramarathon runners, vitamin D supplementation upregulated the expression of miR-155 and miR-223 in blood plasma after the run, in comparison to runners who did not supplement vitamin D [ 139 ]. Karvinen showed that the miR-21 expression found in vesicles changes not only in blood but also in sweat after exercise in comparison to non-exercise conditions (sauna) [ 127 ].…”
Section: Epigenetic Changes Involved In Immune Responsesmentioning
confidence: 99%